Slim Body Weight Is Highly Associated With Enhanced Lipoprotein Functionality, Higher HDL-C, and Large HDL Particle Size in Young Women - Park, Ki-Hoon; Yadav, Dhananjay; Kim, Suk-Jeong; Kim, Jae-Ryong; Cho, Kyung-Hyun (Frontiers in Endocrinology, 2018)
There has been no information about the correlations between body weight distribution and lipoprotein metabolism in terms of high-density lipoproteins-cholesterol (HDL-C) and cholesteryl ester transfer protein (CETP). In this study, we analyzed the quantity and quality of HDL correlations in young women (21.5±1.2-years-old) with a slim (n=21, 46.2±3.8 kg) or plump (n=30, 54.6±4.4 kg) body weight. Body weight was inversely correlated with the percentage of HDL-C in total cholesterol (TC). The plump group showed 40% higher body fat (26±3 %) and 86% more visceral fat mass (VFM, 1.3±0.3 kg) than the slim group, which showed 18±2% body fat and 0.7±0.2 kg of VFM. Additionally, the plump group showed 20% higher TC, 58% higher triglyceride (TG), and 12% lower HDL-C levels in serum. The slim group showed 34% higher apoA-I but 15% lower CETP content in serum compared to the plump group. The slim group showed a 13% increase in particle size and 1.9-fold increase in particle number with enhanced cholesterol efflux activity. Although the plump group was within a normal body mass index (BMI) range, its lipid profile and lipoprotein properties were distinctly different from those of the slim group in terms of CETP mass and activity, HDL functionality, and HDL particle size.